Knowledge associated with the preventive practice of breast cancer in nursing students - Ortiz Montalvo, Yonathan Josué; Vega Tapia, Daniela Carolina; Gonzales Paredes, Maria Celeste; Ortiz Romaní, Katherine Jenny (Horizonte Sanitario, 2023)
Objective: To evaluate the association between knowledge with practice and its dimensions on the prevention of breast cancer in students of the Nursing study program of the Universidad Católica Sedes Sapientiae, 2022. Materials and methods: Cross-sectional and correlationalstudy with a total of 224 Nursing students. Self-administered questionnaires were used to measure the variables. The statistical test was binary logistic regression based on crude odds ratio with 95% confidence interval and its value of ≤ 0.05. Results: Knowledge about breast cancer prevention (OR = 1.77 CI = 1.03 - 3.03 p = 0.038) was associated with practice about breast cancer prevention. In addition, 57.59% of the students know about the prevention of breast cancer and 54.02% presented an inadequate practice. Conclusion: students who know the preventive measures of breast cancer practice it. In addition, a little more than half of the students know about breast cancer, but do not practice it properly. It is recommended that Nursing programs incorporate more courses on public or community health and that both women and men practice early detection measures. Keywords: Knowledge; Breast Self-Examination; Students Nursing.